IMPACTS OF EARNINGS MANAGEMENT ON CORPORATE FAILURE: A CASE STUDY OF WIRECARD - Azim, Md.; Sharif, Md. Jamil (International Journal of Accounting & Finance Review, 2021)
The purpose of this study is to find out whether earnings management has impacts on bankruptcy risk based on the data of Wirecard Company. The M-score of Beneish’s (1999) model has been used to detect the probability of earnings management. On the other hand, the Z"-Score of Altman’s (1968) model has been applied to detect Corporate Failure. Both the models are widely used models in their respective fields. The data from 2002 to 2019 were collected from the annual reports of the Wirecard Company. The result of M-Score indicates that earnings management has a significant impact on the corporate failure (Z-Score) of the company. This finding specifies that a financially distressed firm adopts earnings manipulations. The finding also implies that earnings manipulations harm the financial health of a firm. According to the findings, it can be suggested that to know the financial aspects of a company, both the (Beneish M-model and Altman Z-score model) models could be used concurrently. Beneish M-model is for detecting earnings management and the Altman Z-score model is for determining corporate failure. The novelty of the study is that no study was done on Wirecard Company focusing on the association between earnings management & bankruptcy risk. JEL Classification Codes: G01, G32, G33, M41.